Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.3171/jns.1994.81.4.0507
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord tumors in children: long-term results of combined surgical and radiation treatment

Abstract: The authors report a series of 31 children under 17 years of age with primary spinal cord tumors who underwent radiation treatment following decompression laminectomy with or without tumor resection between 1959 and 1990. The tumors consisted of 15 astrocytomas, 11 ependymomas, one mixed glioma, one gangliolioma, and three of unknown histology. Ten- and 20-year survival rates and 10- and 20-year relapse-free survival rates for the 28 patients with known histology were 80% and 53%, and 73% and 67%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(84 citation statements)
references
References 37 publications
5
74
0
4
Order By: Relevance
“…In addition, pediatric male patients also had significantly better 10-year survival than females in the French study [5], contrary to others [24,30] where adult female patients fared better. Other authors also reported long-term survival in children with HG tumors (over 10 years) [5,9,46,48,54,56] which is rather unusual among adult patients [7,15,27,30,34,35,46,49,51,65]. Thus, it may be possible that pediatric astrocytomas are biologically diverse and the large French study [5] reflected this phenomenon.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, pediatric male patients also had significantly better 10-year survival than females in the French study [5], contrary to others [24,30] where adult female patients fared better. Other authors also reported long-term survival in children with HG tumors (over 10 years) [5,9,46,48,54,56] which is rather unusual among adult patients [7,15,27,30,34,35,46,49,51,65]. Thus, it may be possible that pediatric astrocytomas are biologically diverse and the large French study [5] reflected this phenomenon.…”
Section: Discussionmentioning
confidence: 93%
“…Withholding radiation for infants where spinal cord and skeleton are still developing is also necessary [9]. Longterm survivors after radiotherapy may also be exposed to increased risk of development of a second malignant tumor; 13% risk at 20 years as reported [54]. Some studies also reported decreased survival rates for irradiated patients [56,64]; referral bias for patients in poorer condition to RT may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Intramedullary glioblastoma is uncommon in all ages of life, but in children are extremely rare. [6][7][8] Intramedullary glioblastoma shows a slight predilection for the second and third decades of life, the mean age ranging from 28.5 years in the 20-case series of the Mayo Clinic 9 to 18.1 years according to the review of the literature undertaken by Fortuna in 1971. 10 Our patient was a 6-year-old.…”
Section: Case Reportmentioning
confidence: 99%
“…En compresiones medulares importantes se aprecian además amiotrofias, piramidalismo, arreflexia, etc. En otros casos, la manifestación clínica consiste en la aparición de una tumoración 14,15 hidrocefalia 16 (por liberación masiva de proteínas) o meningismo 17 (rotura de quiste dermoide).…”
Section: Discussionunclassified